Assessment of neonatal glycaemic status and comorbidities in infants of diabetic mothers admitted to the neonatal care unit of Al-Ramadi Teaching Hospital for maternity and childhood, Iraq - Wasnaa Hadi Abdullah; Mohammed Atallah; Basma Adel Ibrahim (Journal of the Pakistan Medical Association, 2024)
Objective: To assess neonatal and maternal characteristics, glycaemic status and comorbidities in the neonates ofdiabetic mothers. Method: The prospective, descriptive study was conducted from March 2021 to December 2021at the neonatal careunit of Al-Ramadi Teaching Hospital for Maternity and Childhood, Iraq, and comprised neonates of diabetic mothersadmitted to the maternity ward or the neonatal care unit. Maternal and neonatal data was collected using aproforma. Blood glucose levels were measured using heel-stick sampling by glucometer in the first 1-3 hours of life. Mild neonatal hypoglycaemia was defined as glucose level less than or equal to 47mg/dL, and severe hypoglycaemia as less than or equal to 36mg/dL.Data was analysed using SPSS 24. Results: Among the 70 mothers, aged between 18 to 44 years, gestational diabetes was the commonest type52(74.3%), and, among the 70 neonates, 52(74.3%) developed mild hypoglycaemia, 12(17.1%) hypocalcaemia, 26(37.1%) congenital heart disease, 50(71.4%) respiratory distress syndrome, 24(34.3%) hyperbilirubinaemia, 2(2.9%) congenital anomalies, 6(8.6%) prematurity, and 4(5.7%) developed birth asphyxia. Prematurity, femalegender and low birthweight were significantly associated with hypoglycaemia (p<0.05). No significant differenceswere detected in terms of neonatal complications between pregestational and gestational diabetic mothers(p>0.05). Conclusions: Diabetic pregnancies were linked to a higher risk of neonatal complications. Key Words: Diabetes, Gestational, Hypocalcemia, Asphyxia, Heel, Jaundice, Chronic Idiopathic, Respiratory Distress,Heart Defects, Congenital.